2018
DOI: 10.3390/rs10071125
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Diurnal/Semidiurnal Atmospheric Tides (S1/S2) and Their Impacts on the Continuous GPS Coordinate Time Series

Abstract: The site displacement due to diurnal and semidiurnal atmospheric tides (S1/S2) is often neglected in the routine precise GPS data processing. We recall the S1/S2 modeling method and show the magnitude of the S1/S2 tides under the Center of Mass (CM) frame. The results show that the annual amplitudes caused by both S1 and S2 tides exceed 1 mm for stations near the equator. The impact of S1/S2 on the 24-h Global Positioning System (GPS) solution is typically at the sub-mm level, and the scatter of the S1/S2 caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, in addition to ATML signals and other known geophysical effects, e.g., continental water storage and non-tidal ocean tidal loading induced displacements (van Dam et al, 1997(van Dam et al, , 2001(van Dam et al, , 2012Fritsche et al, 2012;Williams and Penna, 2011;Yuan et al, 2018), GNSS-related systematic errors also contribute to the observed non-linear variations in GNSS time series (Ray et al, 2008(Ray et al, , 2013. Previous results have shown that imperfect GNSS data processing models and strategies could result in spurious non-linear displacements of GNSS stations, which mask real crustal displacements, thus affecting the comparison between GNSS and predicted loading signals (Deng et al, 2017;Li et al, 2014Li et al, , 2018King and Watson, 2010;Penna and Stewart, 2003;Penna et al, 2007;.…”
Section: Gnss Position Time Seriesmentioning
confidence: 99%
“…However, in addition to ATML signals and other known geophysical effects, e.g., continental water storage and non-tidal ocean tidal loading induced displacements (van Dam et al, 1997(van Dam et al, , 2001(van Dam et al, , 2012Fritsche et al, 2012;Williams and Penna, 2011;Yuan et al, 2018), GNSS-related systematic errors also contribute to the observed non-linear variations in GNSS time series (Ray et al, 2008(Ray et al, , 2013. Previous results have shown that imperfect GNSS data processing models and strategies could result in spurious non-linear displacements of GNSS stations, which mask real crustal displacements, thus affecting the comparison between GNSS and predicted loading signals (Deng et al, 2017;Li et al, 2014Li et al, , 2018King and Watson, 2010;Penna and Stewart, 2003;Penna et al, 2007;.…”
Section: Gnss Position Time Seriesmentioning
confidence: 99%
“…used threshold is the Akaike weight 1%. The results are shown in table 5. One can see that the ratio of the number of sites that can be applied to a model averaging algorithm is all over 50% per direction.…”
Section: Results Of the Analysis Of 110 Worldwide Igs Sitesmentioning
confidence: 96%
“…In recent years, an increasing number of newly built GNSS sites have been put into operation as well, these GNSS sites provide valuable basic data for scientific research. Currently, high-precision GNSS time series obtained through GNSS observations processing are widely used by researchers in scientific research in fields such as geophysics, geology, seismology, geodynamics and atmospheric and marine physics [1][2][3][4][5][6][7][8][9][10][11][12], as well as in infrastructure construction fields such as monitoring of dams, bridges, and tunnels [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The differences interpreted as being related to the representation of atmospheric tides may induce regional biases up to 3 ppm on the mole fraction of methane with respect to dry air averaged over the atmospheric column (see Figure 5). Indeed, time interpolation creates systematic errors for insufficiently sampled periodic components such as atmospheric tides, as it is well documented in other contexts [24].…”
Section: Time Interpolation and Tide Wavesmentioning
confidence: 89%